Sobre subalternidades e enfrentamentos: sexualidade, poder e agenciamentos na experiência de mulheres prostitutas - Andre Geraldo Ribeiro Diniz (2013)
This study aims at identifying and analyzing positions of agency experience among female prostitutes from the bohemian area of Belo Horizonte, in the state of Minas Gerais, Brasil. Thus, the objective is to analyze the conditions of subordination that circumscribe their everyday lives, focusing on the identification of experiences of resistance and assertion of autonomy. The search field is located in the center of the state capital: prostitution hotels in the bohemian area of Belo Horizonte. The methodological strategies consisted of participant observations carried out around Guaicurus Street and of structured interviews with six prostitutes working in that region. The theoretical horizon of the study sought to converge some contributions from Gayle Rubin s political theory of gender, the feminist theories of intersectionality, Foucaults microphysics of power, Charles Taylor s philosophical anthropology, Bourdieu's theory of habitus and Jessé Souzas political sociology. It was built as a dialogue with these authors from assumptions of a feminist epistemology, from the "analysis of experience" (Scott, 1992/2001), and with the prospect of objectivity as "situated research" (Haraway, 1995). The survey results point at an experience marked by profound contradictions and ambiguities. Some elements led to affirming the existence of symbolic struggles around the parameters of differential recognition of prostitutes. There are numerous forces of disqualification that befall them, while the disparity of truths about their condition allows them to build individual and collective strategies of coping. The disqualification of a poor bitch as well as the dynamics of confrontation and resistance, seem to mobilize moral hierarchies (useful and productive work x "the good life"; autonomy x heteronomy), the sexual gender (the whore/holy dichotomy), aesthetic hierarchies etc. What can be said is that constant relationships between markers of various power systems are backdrop to a dynamic of subordination of the prostitutes. The whore/holy dichotomy, the possession of a precarious emotional economy, the device of masculinity, the sexual hierarchies, the lack of legal recognition of prostitution in Brazil and the difficulties of establishing a positive identity that contributes to the politicization of collectivization and their experiences, are some of the elements that allow us to identify the mechanisms of subordination of these women. However, these power devices are frequently questioned by the prostitutes themselves, as they give new meaning to their lives, as well as to their disqualification, to the struggles for solidarity among them, the counter-discourse produced in their everyday lives and the constant affirmation of their autonomy.